PRACTICES OF MANAGING STUDENTS' SOCIO-ECONOMIC STATUS FOR ACHIEVEMENT OF EDUCATIONAL GOALS IN MAKERERE UNIVERSITY (UGANDA) - Mukisa, Elizabeth Juliet; Kimoga, Joseph; Musoke, Gyaviira Genza (International Journal of Psychology, 2021)
Purpose: Prompted by persistent complaints from different stakeholders in regard to the problem of managing diversity of student socio-economic status in Makerere University, the study set out to examine the factors that enable or disable the students from Low Socio-Economic Status (LSES) backgrounds from achieving their educational goals at Makerere University (Uganda). Methodology: The study drew on social justice literature to stimulate debate on why and how such LSES students can be supported to achieve their educational goals. The study adopted a cross-sectional survey design, which was approached from a mixed research paradigm where both qualitative and quantitative data were collected from 410 Makerere University students. Using closed-ended questionnaires and focused interview guides Findings: The study discovered that management practices like financial and material resources mobilization for the underprivileged were absent. It was therefore concluded that practices on socio-economic diversity reflected absence of recognitive and distributive equity. Unique contribution to theory, practice and policy: The study's major contribution lies in the provision of knowledge on up-to-date policies and practices of managing student SES diversity to enable students of a LSES background to achieve their educational goals.